2014
DOI: 10.1111/chd.12165
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Benefit to Postoperative Fluid Restriction Following Infant Surgery?

Abstract: Time to negative fluid balance is not associated with duration of mechanical ventilation, CICU, and hospital length of stay in patients after undergoing systemic-to-pulmonary artery shunt palliation. The utility of a restricted fluid strategy immediately following infant heart surgery is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…19 Nicholson et al questioned the benefit of immediate fluid restriction for infant cardiac surgery. 20 In that study, the authors found that achieving a negative FB in 24 hours was not associated with better outcomes, such as shortened length of ICU or hospital stay. The reduction in caloric intake was significant partly because of restricted fluid intake.…”
Section: Discussionmentioning
confidence: 92%
“…19 Nicholson et al questioned the benefit of immediate fluid restriction for infant cardiac surgery. 20 In that study, the authors found that achieving a negative FB in 24 hours was not associated with better outcomes, such as shortened length of ICU or hospital stay. The reduction in caloric intake was significant partly because of restricted fluid intake.…”
Section: Discussionmentioning
confidence: 92%
“…For bypass cases, fluids are restricted to 50 % of maintenance rates in the immediate postoperative period, whereas in non-bypass cases, it is limited to 60 % of maintenance rates. This fluid regimen should continue until the infant's airway is extubated, after which the fluid rate should increase by 10 % per day [103,104].…”
Section: Special Cases: Cardiac Surgerymentioning
confidence: 99%
“…Regulation of volume and electrolyte homeostasis after cardiac surgery on cardiopulmonary bypass (CPB) in newborns and infants with congenital heart defects (CHD) is challenging [1, 2]. The use of CPB during open heart surgery is accompanied by an inflammatory response leading to capillary leak syndrome (CLS) [35].…”
Section: Introductionmentioning
confidence: 99%